Periodesasi Sejarah Peradaban Islam: Kajian Temporal terhadap Periode Pertengahan dan Modern - Aprilyani, Indah; Nandar, Ade; Enoh, Enoh (Tamadduna: Jurnal Peradaban, 2025)
The history of Islamic civilization is divided into three major periods: the classical, the medieval, and the modern. The classical period marked the peak of Islamic glory and the progress of its civilization. However, during the medieval period, Islam experienced a decline due to various internal and external challenges. In the modern period, Islamic reform movements began to rise as a response to past setbacks. This study aims to interpret the periodization of Islamic civilization by focusing on the medieval and modern periods through a literature review approach. The analysis draws from relevant scholarly works that explore the dynamics of these eras. The findings suggest that both periods can be understood through a temporal lens, examining the driving factors behind their rise and decline as well as key figures who influenced the course of Islamic civilization. This study is expected to offer a comprehensive understanding and serve as a source of inspiration to foster renewed motivation in Islamic propagation.